Agency in schizophrenia and autism: a systematic review - Tan, Denise P. W.; Carter, Olivia; Marshall, Darcy-Rose; Perrykkad, Kelsey (Frontiers in Psychology, 2023)
Previous research suggests that altered experiences of agency are an underlying vulnerability in both schizophrenia and autism. Here, we explore agency as a potential transdiagnostic factor by conducting a systematic review of existing literature investigating agency in autism and schizophrenia individually and together. Results show that, compared to control populations, agency is significantly different in every identified schizophrenia study and generally not significantly different in autism. Importantly, we identified a lack of studies using common tasks and a disproportionate number of studies investigating different dimensions of agency across the two conditions, resulting in limited grounds for valid comparison.